2018
DOI: 10.1101/504670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Metapopulation to Metacommunity and the Complications of Community Structure

Abstract: The metacommunity, as it evolved from Levin's metapopulation, provides a framework to consider the spatial organization of species interactions. Arguably the most fundamental feature of metapopulations and metacommunities are that demes are connected via migration. An important result from Levin's metapopulation work-that increasing migration lowers regional extinction probability-is often incorporated into conceptions of metacommunities. We first use a toy model to show how this result from Levin's metapopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Regardless of whether the results are general or species-specific, recent work indicates that trophic position may strongly influence how dispersal effects the persistence of metacommunities. In a study of tropical terrestrial leaf litter communities, higher rates of dispersal in non-predators caused higher rates of extinction for predator species (Hajian-Forooshani et al, 2019). Our study could indicate that such a pattern exists since aphid prey were observed to have much greater levels of dispersal than natural enemies.…”
Section: Discussionmentioning
confidence: 59%
“…Regardless of whether the results are general or species-specific, recent work indicates that trophic position may strongly influence how dispersal effects the persistence of metacommunities. In a study of tropical terrestrial leaf litter communities, higher rates of dispersal in non-predators caused higher rates of extinction for predator species (Hajian-Forooshani et al, 2019). Our study could indicate that such a pattern exists since aphid prey were observed to have much greater levels of dispersal than natural enemies.…”
Section: Discussionmentioning
confidence: 59%